Reframing remembrance contemporary French cinema and the Second World War - Campbell, Lisa Harper (Manchester : Manchester University Press, 2021)
Reframing remembrance examines films about the Nazi Occupation of France, charting how this period has been commemorated and how it has affected the articulation of French national identity. The book proposes that 1995 marked the beginning of a new approach to commemoration, reflected by socio-political acts, such as Jacques Chirac's July 1995 Vél' d'Hiv speech, and artistic acts, most notably films set during the Occupation. This is an approach that embraces critical engagement with history and its retelling. With relevance to countries beyond France and events far removed from the Second World War, Reframing remembrance highlights the need for ongoing, honest remembrance and self-reflection as cultural representations of history continue to shape contemporary views about nations' identities and their global responsibilities.
Front Matter -- Contents -- Figures -- Acknowledgements -- Note on translations -- Introduction -- 1 Resistance -- 2 Collaboration -- 3 The dichotomy dilemma -- 4 Legacy -- 5 New generations -- Conclusion -- Filmography -- Bibliography -- Index
JSTOR
Keywords: World War, 1939-1945 -- Motion pictures and the war; Motion pictures -- France -- History -- 20th century; Motion pictures -- France -- History -- 21st century; Guerre mondiale, 1939-1945 -- Cinéma et guerre; Cinéma -- France -- Histoire -- 20e siècle.; Cinéma -- France -- Histoire -- 21e siècle.; PERFORMING ARTS / Film & Video / History & Criticism; PERFORMING ARTS / Film / History & Criticism; Motion pictures; War and motion pictures; France; 1900-2099; History